1990
DOI: 10.1111/j.1442-9993.1990.tb01469.x
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive significance of life history characters in selectedorders of marine brown maeroalgae

Abstract: Life history eharaeters. whieh are generally eonsidered to be of eritieal signifteanee in evolution, consist of various pheiiotypie trails eoneerned with growth and reproduetion. Siiite.s ot Hie history eharaeters are frequently referred to as 'strategies'. These are hypotheses whieh attempt to e.xplain the adaptive .signifieanee of partieular suites of eharaeters. This paper reviews lije history eharaeters of speeies belonging to various orders of brown algae (Phaeophyeeae) and diseusses their possible adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 127 publications
0
22
0
Order By: Relevance
“…stricta recolonization has still not recolonized its former habitat . One can hypothesize that the lack of recolonization in disturbed areas could be explained by a small dispersal range and therefore by recruitment being linked to the presence of reproductive individuals in the neighborhood, as reported by Clayton (1990) for the order Fucales. Since natural restoration has never occurred, we propose to develop a technique for recolonization of impacted areas.…”
mentioning
confidence: 93%
“…stricta recolonization has still not recolonized its former habitat . One can hypothesize that the lack of recolonization in disturbed areas could be explained by a small dispersal range and therefore by recruitment being linked to the presence of reproductive individuals in the neighborhood, as reported by Clayton (1990) for the order Fucales. Since natural restoration has never occurred, we propose to develop a technique for recolonization of impacted areas.…”
mentioning
confidence: 93%
“…The fucoid algae that surround Durvillaea habitats are relatively poor dispersers due to their relatively large egg sizes (Clayton 1990, 1992, Chapman 1995. Consequently, zygotes rarely settle more than a few meters from adult plants (D.I.T.…”
Section: Interspecific Interactionsmentioning
confidence: 99%
“…The adult plants have perennial thalli, with a basal meristem and strap-like lamina closely resembling Laminaria species from the Northern Hemisphere (Clayton, 1990). Laboratory studies under simulated Antarctic daylength conditions have shown A. mirabilis to be welladapted to the Antarctic light regime, characterized by strong seasonal variations of daylength and irradiance.…”
Section: Introductionmentioning
confidence: 99%